Implementasi Pembelajaran PAI Berwawasan Nilai-Nilai Tatas Tuhu Trasna Di SMP Islam Nurul Qur’an Lombok Tengah - M Khaerul Insan; Rahmat (4, 2026)
This study aims to describe and analyze the implementation of Islamic Religious Education (PAI) learning based on the Tatas Tuhu Trasna values ​​at Nurul Qur'an Islamic Junior High School, Central Lombok. The Tatas Tuhu Trasna values ​​are the local wisdom of the Lombok community that contain the meaning of order and discipline (Tatas), sincerity and responsibility (Tuhu), and compassion and concern for others (Trasna). The integration of these values ​​in PAI learning is expected to strengthen the character formation of students who are religious, have noble morals, and have social awareness. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation involving the principal, PAI teachers, students, and other related parties as research informants. The data obtained are analyzed using the Miles and Huberman interactive analysis model which includes data reduction, data presentation, and drawing conclusions. Data validity is tested through triangulation of sources, techniques, and time. The results of the study indicate that the implementation of Islamic Religious Education learning based on Tatas Tuhu Trasna values ​​is carried out through the integration of these values ​​into the planning, implementation, and evaluation of learning, as well as through habituation and school culture. Tatas values ​​are realized through the formation of discipline and compliance with school rules, Tuhu values ​​through the instilling of responsibility, honesty, and sincerity in learning, while Trasna values ​​are realized through attitudes of mutual respect, care, and affection among school members. This implementation is supported by teacher role models, a religious school environment, and cooperation between the school and parents. The obstacles faced include the influence of technological developments, student social interactions, and differences in family backgrounds. Overall, the implementation of Islamic Religious Education learning based on Tatas Tuhu Trasna values ​​has been proven to strengthen the formation of students' religious and social character and support the creation of a harmonious and cultural educational environment. Abstrak Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis implementasi pembelajaran Pendidikan Agama Islam (PAI) berwawasan nilai-nilai Tatas Tuhu Trasna di SMP Islam Nurul Qur’an Lombok Tengah. Nilai-nilai Tatas Tuhu Trasna merupakan kearifan lokal masyarakat Lombok yang mengandung makna ketertiban dan kedisiplinan (Tatas), kesungguhan dan tanggung jawab (Tuhu), serta kasih sayang dan kepedulian terhadap sesama (Trasna). Integrasi nilai-nilai tersebut dalam pembelajaran PAI diharapkan mampu memperkuat pembentukan karakter peserta didik yang religius, berakhlak mulia, dan memiliki kepedulian sosial. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi dengan melibatkan kepala sekolah, guru PAI, peserta didik, serta pihak terkait lainnya sebagai informan penelitian. Data yang diperoleh dianalisis menggunakan model analisis interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data diuji melalui triangulasi sumber, teknik, dan waktu. Hasil penelitian menunjukkan bahwa implementasi pembelajaran PAI berwawasan nilai-nilai Tatas Tuhu Trasna dilakukan melalui integrasi nilai-nilai tersebut ke dalam perencanaan, pelaksanaan, dan evaluasi pembelajaran, serta melalui pembiasaan dan budaya sekolah. Nilai Tatas diwujudkan melalui pembentukan sikap disiplin dan kepatuhan terhadap aturan sekolah, nilai Tuhu melalui penanaman tanggung jawab, kejujuran, dan kesungguhan dalam belajar, sedangkan nilai Trasna diwujudkan melalui sikap saling menghormati, peduli, dan kasih sayang antarwarga sekolah. Implementasi tersebut didukung oleh keteladanan guru, lingkungan sekolah yang religius, serta kerja sama antara sekolah dan orang tua. Adapun kendala yang dihadapi antara lain pengaruh perkembangan teknologi, pergaulan peserta didik, dan perbedaan latar belakang keluarga. Secara keseluruhan, implementasi pembelajaran PAI berwawasan nilai-nilai Tatas Tuhu Trasna terbukti mampu memperkuat pembentukan karakter religius dan sosial peserta didik serta mendukung terciptanya lingkungan pendidikan yang harmonis dan berbudaya.